Careers if you like the creative arts - Kallen, Stuart A., 1955- (Career exploration (ReferencePoint Press), 2020)
Introduces a variety of careers in the creative arts field, providing information about educational requirements, job duties, work environments, salaries, and employment outlook. Includes color photographs, an interview with a professional in the field, and quotes.